Gestión administrativa y la calidad del servicio en el GAD Municipal de Pangua en el periodo 2019-2023 - Mejía Herrera, Diego Xavier (2023)
The purpose of this research work is to analyze the administrative management and the quality of the service of the Municipal GAD of Pangua in the administrative period 2019-2023; through a situational analysis and direct inquiry to the actors involved. It was carried out under the thematic axes of Administrative Management and Quality of Service, understanding that the final and essential purpose of the public sector is the quality of service. The methodology was based on the quantitative approach, of a descriptive type, carried out with on-site visits to the departments belonging to the municipal GAD of the canton and its parishes, surveys were applied to a sample of 377 people belonging to the parishes of the canton and 6 departmental heads. . The results reflected in terms of Administrative Management are acceptable in 73.44% and the Quality of Service is admitted in 88.72% of the general population of the canton; however, 11.28% are dissatisfied with the administrative management and 26.56% disagree with the quality of service provided by the municipality, therefore, there is a gap that is suggested to strengthen the behavior of human capital by deepening knowledge of the public function that allows internalizing its importance. For which a training plan is proposed that raises the criteria of quality of service in the GAD Pangua.